The impact of strategic marketing on enterprise competitiveness - Musaeva, Rushana A. (Цифровой бренд-менеджмент территорий: глобальный и локальный аспекты : материалы IV Международной трансдисциплинарной научно-практической Web-конференции "Connect-Universum-2018", 29–30 ноября 2018 года)
Today, the problem of the enterprise's competitiveness is more urgent than ever for the national economy and for its economic entities - enterprises. It is important to determine what extent the enterprise is competitive with other entities in this market, since a high degree of competitiveness is a guarantee of obtaining high economic indicators in the current market conditions, and have a strategic goal of achieving a level that would help it survive in a tough competitive environment. In this regard, the article describes the role of marketing strategy in the development of the enterprise and outlines the main problems associated with the competitiveness of the enterprise. The external and internal factors that are the most popular among modern economists are considered. The modern competitive environment is a complex and dynamically changing system, which necessitates the continuous improvement of methods for managing the competitiveness of enterprises. In this paper, we also discuss in detail the basic concepts of strategic marketing and its use to enhance the competitiveness of the enterprise and the country as a whole. In this regard, the main functions and tasks of strategic marketing are researched and a system of interethnic relations between models of strategic marketing and enterprise competitiveness is proposed. The proposed system allows classifying the methods of quantitative solution to ensure competitiveness. The main points of how a marketing strategy should be carried out are also given.